Examining operational challenges and external factors influenceing the Garden City Multi-Purpose Cooperative in Guiguinto, Bulacan - Pineda, Carlos Joaquin D.; Tumangan, John Neil D.A
This study examined operational challenges and the influence of negative externalities on plant nursery businesses within the Garden City Multi-Purpose Cooperative, Guiguinto, Bulacan. The research investigated how external factors--traffic congestion, flooding and infrastructure limitations-- and internal aspects like marketing and financial literacy impact these businesses. Economic concepts of opportunity cost, externalities, market failure, and organizational persistence framed the study. Data were collected through surveys and interviews with ten plant nursery owners-- five cooperative, five non-members--via purposive sampling. Specifically, it aimed to (1) measure revenue losses or opportunity costs due to traffic, (2) describe how plant nursery businesses cope with traffic congestion, and (3) identify additional operational challenges.